2023
DOI: 10.3171/2023.1.jns222804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carotid revascularization on cognitive function and brain functional connectivity in carotid stenosis patients with cognitive impairment: a pilot study

Abstract: OBJECTIVE Carotid stenosis can lead to both cognitive impairment (CI) and ischemic stroke. Although carotid revascularization surgery, which includes carotid endarterectomy (CEA) and carotid artery stenting (CAS), can prevent future strokes, its effect on cognitive function is controversial. In this study, the authors examined resting-state functional connectivity (FC) in carotid stenosis patients with CI undergoing revascularization surgery, with a particular focus on the default mode network (DMN). METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Increasing evidence suggests that CEA/CAS can lead to neurocognitive improvements. [22][23][24] In patients with severe carotid stenosis, baseline measures of cognitive function may be below the normal levels observed in the general population; 25) however, whether elderly patients experience neurocognitive improvements following CEA/CAS remains controversial. For example, a study by Succar et al suggested that carotid interventions improved cognitive function in younger patients with carotid occlusive atherosclerosis, whereas no cognitive benefits were observed in males above 80 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that CEA/CAS can lead to neurocognitive improvements. [22][23][24] In patients with severe carotid stenosis, baseline measures of cognitive function may be below the normal levels observed in the general population; 25) however, whether elderly patients experience neurocognitive improvements following CEA/CAS remains controversial. For example, a study by Succar et al suggested that carotid interventions improved cognitive function in younger patients with carotid occlusive atherosclerosis, whereas no cognitive benefits were observed in males above 80 years old.…”
Section: Discussionmentioning
confidence: 99%